Application de la méthode X-FEM à la résolution de problèmes de micromécanique - Cartraud, Patrice; Cloirec, Mathieu; Moës, Nicolas (European Journal of Computational Mechanics, 2004)
The eXtended Finite Element Method (X-FEM) allows one to enrich finite element approximation space, thus accounting for discontinuities inside an element. This method is applied in this paper to the solution of micromechanical problem, in order to simplify the mesh generation, since it does not need to conform to the material interfaces. A new enrichment function is proposed, which turns out to have the same accuracy as the classical finite element method. Numerical experiments are presented, for material applications, and for a strandedrope structure.